A nanosheet and its preparation method and its application in a blended all-vanadium liquid flow battery membrane

By blending and doping nanosheets with polybenzimidazole, nanosheets with high specific surface area are prepared and used as separators for all-vanadium redox flow batteries. This solves the problem of slow proton transfer in existing separators at high current densities and achieves Efficient voltage and Coulomb efficiency improvements.

CN116023655BActive Publication Date: 2025-01-21CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310011216.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-05
Publication Date
2025-01-21
Estimated Expiration
2043-01-05

AI Technical Summary

Technical Problem

The existing all-vanadium flow cell separators have slow proton transfer rates under high current density, which makes the battery unable to work effectively, and the commercial Nafion membrane is expensive and the vanadium ion permeability is high.

Method used

Nanosheets are blended and doped with polybenzimidazole, and the narrow channels and high specific surface area characteristics of the nanosheets are used to improve the ion selectivity and vanadium blocking ability of the separator, and enhance the voltage efficiency and Coulombic efficiency of the battery.

Benefits of technology

It achieves improvements in high voltage efficiency and Coulombic efficiency, significantly improves the vanadium blocking ability of the separator and vanadium ion permeability, reduces the cost of the battery, and maintains the proton transfer capability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116023655B_ABST
    Figure CN116023655B_ABST
Patent Text Reader

Abstract

The present invention provides a nanosheet and a preparation method thereof and an application in a blended all-vanadium liquid flow battery membrane, belonging to the fields of two-dimensional nanomaterial preparation technology and all-vanadium liquid flow battery diaphragm technology. The present invention utilizes the auxiliary effect of a surfactant so that the water-oil two-phase monomers participating in the diazo coupling reaction at the microphase interface can be evenly distributed at the interface, so that the pores of the obtained porous organic polymer skeleton are more regular; in addition, the interface confinement effect of the water-oil two-phase will inhibit the growth of the diazo coupling reaction in the longitudinal direction, thereby obtaining a nanosheet material with a high specific surface area and two-dimensional properties. Due to the confinement effect of the narrow pores, the penetration of vanadium ions can be effectively inhibited, and the ion selectivity of the membrane can be improved. Moreover, because the nanosheet has a rich pore structure, it can not affect the transfer of protons, so that the blended all-vanadium liquid flow battery can obtain higher performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical fields of two-dimensional nanomaterial preparation technology and all-vanadium redox flow battery membrane, and specifically relates to a nanosheet and a preparation method thereof and application in a blended all-vanadium redox flow battery membrane. Background Art

[0002] Energy is one of the crucial material foundations driving the development of modern society. Due to the non-renewable nature of fossil fuels and the significant environmental impacts associated with their combustion, promoting an energy revolution and adopting renewable energy sources such as nuclear power, hydropower, wind power, and solar power as the primary energy sources of the future is crucial for alleviating the energy crisis at its source. To effectively utilize these renewable energy sources, we must focus on new energy storage technologies.

[0003] Currently, the main energy storage technologies being developed can be divided into two categories: physical energy storage and chemical energy storage. Although physical energy storage has the characteristics of high capacity and low cost, it often requires special terrain or large infrastructure to implement, which is not conducive to the energy storage model of future new energy sources. All-vanadium liquid flow batteries, as one of the most promising chemical energy storage technologies, are widely used due to their high efficiency, long life, good safety, and flexible design. At present, most vanadium liquid flow batteries use commercial Nafion membranes, but these membranes are expensive and have high vanadium ion permeability, so there is a need to develop high-performance and inexpensive battery separators. Polybenzimidazole is widely used in all-vanadium liquid flow batteries because of its high chemical stability, especially in strong acid and strong oxidizing environments. However, its proton transfer rate is slow at high current density, resulting in battery inoperability. Therefore, it is of great research significance to modify the highly chemically stable polybenzimidazole membrane and improve its voltage efficiency.

[0004] Adding porous materials to polybenzimidazole membranes is one of the key approaches to achieving high coulombic and voltage efficiency. Patent No. CN 110429293B reports a vanadium redox flow battery separator made of polybenzimidazole doped with a covalent organic framework. The pore size of the covalent organic framework is used to block the permeation of vanadium ions. Increasing the specific surface area of ​​the doped material can effectively block vanadium permeation while enhancing proton transport. Therefore, the preparation of porous materials with high specific surface areas and their application in vanadium redox flow battery separators is of great significance. Summary of the Invention

[0005] The purpose of the present invention is to provide a nanosheet, a preparation method thereof and an application in a blended all-vanadium liquid flow battery membrane. The nanosheet is doped with polybenzimidazole to obtain a blended all-vanadium liquid flow battery membrane material. The nanosheet has a small pore size to improve the vanadium resistance. At the same time, the nanosheet has a high surface area, which can reduce its effect on proton transfer, thereby achieving high battery coulombic efficiency and high voltage efficiency.

[0006] The technical solutions adopted by the present invention to solve the technical problems are as follows:

[0007] The present invention first provides a nanosheet, the structural formula of which is shown in Formula 1:

[0008]

[0009] The present invention also provides a method for preparing a nanosheet, comprising:

[0010] Step (1): adding 1,3,5-tris(4-aminophenyl)benzene monomer to water, adding inorganic acid thereto, mechanically stirring to completely dissolve it, and placing it in an environment of 0 to 10° C. to obtain 1,3,5-tris(4-aminophenyl)benzene solution A;

[0011] Step (2): adding the prepared sodium nitrite aqueous solution dropwise to the 1,3,5-tris(4-aminophenyl)benzene solution A described in step (1), maintaining the temperature of the 1,3,5-tris(4-aminophenyl)benzene solution A at 0-10° C., stirring for 10-30 minutes, and obtaining a diazonium salt solution B;

[0012] Step (3): adding an inorganic base solution to the diazonium salt solution B in step (2), adjusting the pH of the diazonium salt solution B to 1 to 14, then adding a surfactant, and stirring to obtain a diazonium salt solution C;

[0013] Step (4): preparing a pyrogallol organic solution to obtain an organic solution D;

[0014] Step (5): adding the organic solution D in step (4) dropwise to the diazonium salt solution C in step (3), stirring vigorously for 0.05 to 240 hours at a stirring speed of 100 to 8000 rpm, and maintaining the mixed solution at 0 to 10° C., and performing post-treatment to obtain nanosheets.

[0015] Preferably, in the step (1), the mass percentage concentration of the 1,3,5-tris(4-aminophenyl)benzene monomer is 0.01 to 50 wt%, and the volume fraction of the inorganic acid is 0.01 to 20 v / v%.

[0016] Preferably, the inorganic acid in step (1) is concentrated hydrochloric acid, concentrated sulfuric acid, concentrated nitric acid, or tetrafluoroboric acid.

[0017] Preferably, in step (2), the ratio of the amount of sodium nitrite to the amount of 1,3,5-tris(4-aminophenyl)benzene is (3-10):1.

[0018] Preferably, in step (3), the inorganic alkaline solution is lithium hydroxide, sodium hydroxide, potassium hydroxide, cesium hydroxide), barium hydroxide, calcium hydroxide, aluminum hydroxide, magnesium hydroxide, zinc hydroxide, copper hydroxide, iron hydroxide, lead hydroxide, cobalt hydroxide, chromium hydroxide, zirconium hydroxide, nickel hydroxide, ammonium hydroxide, sodium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate or cesium carbonate.

[0019] Preferably, in step (3), the surfactant is sodium oleate, stearylamine, sodium laurate, coconut amine, sodium stearate, AES, sodium lauryl sulfate, dodecylamine, sodium dodecylbenzenesulfonate, dodecyltrimethylammonium chloride or dodecyltrimethylammonium bromide.

[0020] Preferably, in step (3), the mass ratio of the surfactant to the 1,3,5-tris(4-aminophenyl)benzene monomer is (0.001-1):1.

[0021] Preferably, in step (4), the concentration of the pyrogallol organic solution is 0.001 to 5 mol / L.

[0022] The principle of the present invention is: the diazonium salt of 1,3,5-tris(4-aminophenyl)benzene used in the present invention can react with pyrogallol to produce a diazo coupling reaction in an alkaline environment, and its reaction site is the adjacent position of the phenolic hydroxyl group of pyrogallol; due to the high reactivity of the diazonium salt, the diazonium salt solution and pyrogallol can be placed in the water-oil two-phase, thereby utilizing the confinement effect of the water-oil interface to inhibit its growth in the longitudinal direction; in addition, adding a surfactant to the reaction system can make the monomers in the water-oil two-phases evenly arranged at the interface, and prepare a high specific surface area nanosheet with two-dimensional properties; the prepared high specific surface area nanosheet can be doped with polybenzimidazole to prepare a blended all-vanadium liquid flow battery membrane, utilizing the confinement effect of narrow pores to improve ion selectivity, inhibit the penetration of vanadium ions, and obtain an improvement in the battery performance of the all-vanadium liquid flow battery. Figure 1 As shown, the narrow pores of the nanosheets make it difficult for vanadium ions to pass through, thus achieving its vanadium barrier properties.

[0023] Beneficial effects of the present invention

[0024] The purpose of the present invention is to provide a nanosheet, a preparation method thereof, and its application in a blended all-vanadium redox flow battery membrane. The present invention utilizes the auxiliary effect of a surfactant to uniformly distribute the water-oil two-phase monomers participating in the diazo coupling reaction at the microphase interface, thereby making the pores of the resulting porous organic polymer skeleton more regular. In addition, the interfacial confinement of the water-oil two-phase will inhibit the growth of the diazo coupling reaction in the longitudinal direction, thereby obtaining a nanosheet material with a high specific surface area and two-dimensional properties. The high specific surface area nanosheet material prepared by this method has a BET specific surface area of ​​up to 1204.9 m2 g -1 , far exceeding the porous organic polymer materials reported so far. By blending and doping this high-specific-surface-area nanosheet with polybenzimidazole, a highly compatible blended all-vanadium redox flow battery membrane can be obtained. Furthermore, the confinement of the narrow pores effectively inhibits the permeation of vanadium ions, improving the membrane's ion selectivity. Furthermore, the nanosheet's rich pore structure does not affect proton transport, thereby enabling the blended all-vanadium redox flow battery to achieve higher performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The diagram is a chemical structure diagram of the prepared high specific surface area nanosheets and a diagram of the vanadium barrier principle;

[0026] Figure 2 An atomic force microscope image of a high specific surface area nanosheet prepared by the method of Example 1 of the present invention and a thickness diagram of the nanosheet;

[0027] Figure 3 This is the nitrogen adsorption-desorption curve of the high specific surface area nanosheets of Example 2 of the present invention at 77K;

[0028] Figure 4 This is the X-ray diffraction spectrum of the high specific surface area nanosheets of Example 3 of the present invention;

[0029] Figure 5 This is a physical picture of the blended all-vanadium liquid flow battery membrane doped with high specific surface area nanosheets according to Example 1 of the present invention. DETAILED DESCRIPTION

[0030] The present invention first provides a nanosheet, the structural formula of which is shown in Formula 1:

[0031]

[0032] The present invention also provides a method for preparing a nanosheet, comprising:

[0033] The present invention also provides a method for preparing a nanosheet, comprising:

[0034] Step (1): adding 1,3,5-tris(4-aminophenyl)benzene monomer to water, adding inorganic acid thereto, and mechanically stirring to completely dissolve it, wherein the stirring time is preferably 10 to 30 minutes, more preferably 12 to 25 minutes, and placing it in an environment of 0 to 10°C, preferably 1 to 7°C, to obtain 1,3,5-tris(4-aminophenyl)benzene solution A; the mass percentage concentration of the 1,3,5-tris(4-aminophenyl)benzene monomer is preferably 0.01 to 50wt%, more preferably 3 to 33wt%, and the volume fraction of the inorganic acid is preferably 0.01 to 20v / v%, more preferably 3 to 15v / v%, and the inorganic acid is concentrated hydrochloric acid, concentrated sulfuric acid, concentrated nitric acid, or tetrafluoroboric acid.

[0035] Step (2): preparing a sodium nitrite aqueous solution with a mass concentration of preferably 0.1 to 10 w / v%, preferably a mass concentration of 0.2 to 5 w / v%, wherein the ratio of the amount of sodium nitrite to the amount of 1,3,5-tris(4-aminophenyl)benzene is preferably (3 to 10):1, more preferably 3.2 to 7:1, and adding the prepared sodium nitrite aqueous solution dropwise to the 1,3,5-tris(4-aminophenyl)benzene solution A described in step (1), maintaining the temperature of the 1,3,5-tris(4-aminophenyl)benzene solution A at 0 to 10° C., preferably 5 to 7° C., stirring for 10 to 30 minutes, preferably 15 to 25 minutes, to obtain a diazonium salt solution B;

[0036] Step (3): adding an inorganic base solution to the diazonium salt solution B in step (2), adjusting the pH of the diazonium salt solution B to 1 to 14, preferably 8 to 12, and adding a surfactant, wherein the mass ratio of the surfactant to the 1,3,5-tris(4-aminophenyl)benzene monomer is preferably (0.001 to 1):1, more preferably 0.01 to 0.3:1, and stirring thoroughly to obtain a diazonium salt solution C; the mass concentration of the inorganic base solution is preferably 0.1 to 10 w / v%, more preferably 0.9 to 5 w / v%;

[0037] The inorganic base is preferably lithium hydroxide, sodium hydroxide, potassium hydroxide, cesium hydroxide), barium hydroxide, calcium hydroxide, aluminum hydroxide, magnesium hydroxide, zinc hydroxide, copper hydroxide, iron hydroxide, lead hydroxide, cobalt hydroxide, chromium hydroxide, zirconium hydroxide, nickel hydroxide, ammonium hydroxide, sodium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate, or cesium carbonate.

[0038] The surfactant is preferably sodium oleate, stearylamine, sodium laurate, coconut amine, sodium stearate, AES, sodium lauryl sulfate, dodecylamine, sodium dodecylbenzenesulfonate, dodecyltrimethylammonium chloride, and dodecyltrimethylammonium bromide.

[0039] Step (4): preparing a pyrogallol organic solution to obtain an organic solution D; the concentration of the pyrogallol organic solution is preferably 0.001 to 5 mol / L, more preferably 0.01 to 4 mol / L;

[0040] The organic solvent used to prepare the organic solution is preferably benzene, toluene, chlorobenzene, xylene, mesitylene, dichloromethane, chloroform, tetrachloromethane, methyl formate, ethyl formate, propyl formate, butyl formate, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, propyl propionate, butyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate, and butyl butyrate.

[0041] Step (5): adding the organic solution D in step (4) dropwise to the diazonium salt solution C in step (3), vigorously stirring for 0.05 to 240 hours, preferably 0.5 to 196 hours, at a stirring speed of 100 to 8000 rpm, preferably 900 to 3000 rpm, and maintaining the mixed solution at 0 to 10° C., preferably 2 to 7° C., to obtain a crude product of high specific surface area nanosheets, preferably separating the crude product of high specific surface area nanosheets from the mixed solution by filtration, and washing the crude product of high specific surface area nanosheets with an organic solution, and finally drying the washed nanosheets to obtain nanosheets.

[0042] In step (5), the organic solution used to wash the high specific surface area nanosheets is benzene, toluene, chlorobenzene, xylene, mesitylene, dichloromethane, chloroform, tetrachloromethane, methyl formate, ethyl formate, propyl formate, butyl formate, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, propyl propionate, butyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate, butyl butyrate, N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone.

[0043] The present invention also provides the use of the nanosheets in a blended all-vanadium liquid flow battery membrane.

[0044] Preferably, the method for preparing the blended all-vanadium liquid flow battery membrane comprises:

[0045] Step 1: The high specific surface area nanosheets obtained above are dispersed in an organic solvent by ultrasonic treatment. The mass percentage of the high specific surface area nanosheets to the organic solvent is preferably 0.01-20wt%, more preferably 1-5wt%. The dispersion method is not particularly limited, but is preferably ultrasonic. The ultrasonic treatment time is preferably 1-480 minutes, more preferably 135-180 minutes, to obtain an organic solvent dispersion of high specific surface area nanosheets. The organic solvent for dispersing the high specific surface area nanosheets is preferably N,N-dimethylformamide, N,N-dimethylacetamide, or N-methylpyrrolidone.

[0046] Step 2: Mixing the high specific surface area nanosheet organic solvent dispersion in step 1 with the polybenzimidazole solution and stirring evenly, wherein the mass percentage of the polybenzimidazole solution after mixing is preferably 0.1 to 50 wt%, and the mass ratio of the nanosheets to the polymer polybenzimidazole is preferably (0.005 to 0.4):1, more preferably 0.008-0.2:1, to obtain a casting solution G, wherein the mass percentage of the polybenzimidazole solution is preferably 0.1 to 20 wt%, more preferably 5-17 wt%;

[0047] The structure of polybenzimidazole is as follows:

[0048]

[0049] Step 3: The casting solution of step 2 is used to prepare a blended all-vanadium redox flow battery separator using a tape casting machine. The thickness of the blended all-vanadium redox flow battery separator is preferably 1 to 1000 microns, more preferably 45 to 60 microns.

[0050] The high specific surface area nanosheets prepared by the diazo coupling reaction provided by the present invention have a high specific surface area of ​​1204.9 m due to the addition of surfactants during the microphase interface polymerization process. Therefore, during the reaction, the monomers in the water and oil phases can be evenly dispersed on both sides of the interface to form nanosheets with a relatively regular framework structure. 2 g -1 , and a thickness of only 2.9nm. Because microphase interfaces can provide a rich water-oil interface, this reaction has the potential to be mass-produced. The resulting high-surface-area nanosheets can be used as nanofillers and blended with polybenzimidazole to prepare blended all-vanadium redox flow battery membranes.

[0051] The present invention is further described in detail below with reference to the examples.

[0052] Example 1

[0053] Add 1,3,5-tris(4-aminophenyl)benzene monomer with a mass percentage concentration of 15wt% to water, then add hydrochloric acid with a volume fraction of 6v / v%, mechanically stir for 12 minutes to completely dissolve it, and place it in an environment of 1°C to obtain a 1,3,5-tris(4-aminophenyl)benzene solution for standby use. Prepare a sodium nitrite aqueous solution with a mass concentration of 3w / v%, wherein the ratio of the amount of sodium nitrite to the amount of 1,3,5-tris(4-aminophenyl)benzene is 5.5:1. Add the prepared sodium nitrite aqueous solution dropwise to the above-mentioned 1,3,5-tris(4-aminophenyl)benzene solution, maintain the temperature of the 1,3,5-tris(4-aminophenyl)benzene solution at 5°C, and stir for 30 minutes to obtain a diazonium salt solution. A 0.9 w / v % cesium carbonate solution was added to the diazonium salt solution. The pH of the diazonium salt solution was adjusted to 12. Sodium laurate was then added at a mass ratio of 0.01:1 between sodium laurate and 1,3,5-tris(4-aminophenyl)benzene monomer. The mixture was stirred thoroughly and set aside. A 0.55 mol / L pyrogallol / ethyl propionate solution was prepared. The pyrogallol / ethyl propionate solution was added dropwise to the surfactant-containing diazonium salt solution. The mixture was stirred vigorously for 180 hours at 900 rpm, while maintaining the temperature at 7°C. This yielded a high-specific-surface-area crude nanosheet product. The high-specific-surface-area crude nanosheet product was separated from the mixed solution by filtration and washed with tetrachloromethane. Finally, the washed nanosheets were dried to yield high-specific-surface-area nanosheets.

[0054] The resulting high-surface-area nanosheets were dispersed in N-methylpyrrolidone via ultrasonic treatment. The mass ratio of the high-surface-area nanosheets to the N-methylpyrrolidone was 5 wt%, and the ultrasonic treatment lasted for 180 minutes, resulting in a dispersion of the high-surface-area nanosheets in N-methylpyrrolidone. A 14 wt% polybenzimidazole solution was prepared. The resulting N-methylpyrrolidone dispersion of the high-surface-area nanosheets was mixed with the polybenzimidazole solution and stirred evenly. After mixing, the polybenzimidazole solution was 5 wt%, and the mass ratio of the nanosheets to the polymer was 0.008:1, resulting in a casting solution. The casting solution was then used to form a 55-micron-thick blended all-vanadium redox flow battery separator using a tape casting machine.

[0055] The prepared ultrathin nanosheets were tested and their BET specific surface area was 976.5 m 2 g -1 , the pore size is mainly distributed at 0.8 nm, and the thickness of the nanosheet is 3.3 nm.

[0056] Testing the VO2 of blended all-vanadium redox flow battery membrane 2+ The vanadium ion permeability coefficient is 5.39×10 -7 cm 2 min-1 .

[0057] The blended all-vanadium redox flow battery membrane was tested in an all-vanadium redox flow battery at a working current density of 80 mA cm -2 Under constant current charge and discharge conditions, the test results show a coulombic efficiency of 94% and an energy efficiency of 75.1%.

[0058] Figure 2 The atomic force microscope image (left) and the thickness diagram of the nanosheet (right) of the high specific surface area nanosheet prepared by the method of Example 1 of the present invention are shown. Figure 2 It shows that the prepared nanosheets have a scale of hundreds of nanometers and a thickness of 2.9 nanometers;

[0059] Figure 5 This is a physical picture of the blended all-vanadium liquid flow battery membrane doped with high specific surface area nanosheets according to Example 1 of the present invention. The picture shows that the nanosheets and the polymer have good compatibility and it is difficult to find obvious incompatible sites.

[0060] Example 2

[0061] Add 1,3,5-tris(4-aminophenyl)benzene monomer with a mass percentage concentration of 3wt% to water, then add hydrochloric acid with a volume fraction of 3v / v%, mechanically stir for 12 minutes to completely dissolve it, and place it in an environment of 3°C to obtain a 1,3,5-tris(4-aminophenyl)benzene solution for standby use. Prepare a sodium nitrite aqueous solution with a mass concentration of 1w / v%, wherein the ratio of the amount of sodium nitrite to the amount of 1,3,5-tris(4-aminophenyl)benzene is 3.2:1. Add the prepared sodium nitrite aqueous solution dropwise to the above-mentioned 1,3,5-tris(4-aminophenyl)benzene solution, maintain the temperature of the 1,3,5-tris(4-aminophenyl)benzene solution at 5°C, and stir for 15 minutes to obtain a diazonium salt solution. A 1.5 w / v% sodium carbonate solution was added to the diazonium salt solution. The pH of the diazonium salt solution was adjusted to 8. Sodium lauryl sulfate was then added at a mass ratio of 0.001:1 between sodium lauryl sulfate and 1,3,5-tris(4-aminophenyl)benzene monomer. The mixture was stirred thoroughly and set aside. A 0.01 mol / L pyrogallol / butyl butyrate solution was prepared. The pyrogallol / butyl butyrate solution was added dropwise to the surfactant-containing diazonium salt solution. The mixture was stirred vigorously for 24 hours at 1000 rpm, while the temperature of the mixture was maintained at 5°C. This yielded a high-specific-surface-area crude nanosheet product. The high-specific-surface-area crude nanosheet product was separated from the mixed solution by filtration and washed with tetrachloromethane. Finally, the washed nanosheets were dried to yield high-specific-surface-area nanosheets.

[0062] The resulting high-surface-area nanosheets were dispersed in N,N-dimethylformamide via ultrasonic treatment. The mass ratio of the high-surface-area nanosheets to the N,N-dimethylformamide was 1 wt%, and the ultrasonic treatment lasted for 135 minutes, resulting in a dispersion of the high-surface-area nanosheets in N-methylpyrrolidone. A 17 wt% polybenzimidazole solution was prepared. The resulting N,N-dimethylformamide dispersion of the high-surface-area nanosheets was mixed with the polybenzimidazole solution and stirred until the mass ratio of the polybenzimidazole solution was 5.5%. The mass ratio of the nanosheets to the polymer was 0.02:1, resulting in a casting solution. This casting solution was then used to form a 60-micron-thick blended all-vanadium redox flow battery separator using a tape casting machine.

[0063] The prepared ultrathin nanosheets were tested and their BET specific surface area was 1204.9 m 2 g -1 , the pore size is mainly distributed at 0.6 nm, and the thickness of the nanosheet is 2.9 nm.

[0064] Testing the VO2 of blended all-vanadium redox flow battery membrane 2+ The vanadium ion permeability coefficient is 4.39×10 -7 cm 2 min -1 .

[0065] The blended all-vanadium redox flow battery membrane was tested in an all-vanadium redox flow battery at a working current density of 80 mA cm -2 Under constant current charge and discharge conditions, the test results show a coulombic efficiency of 98% and an energy efficiency of 84.1%.

[0066] Figure 3 This is the nitrogen adsorption-desorption curve of the high specific surface area nanosheet of Example 2 of the present invention at 77K, which shows that the nanosheet has a relatively high porosity structure.

[0067] Example 3

[0068] Add 33wt% 1,3,5-tris(4-aminophenyl)benzene monomer to water, add 8v / v% hydrochloric acid thereto, stir mechanically for 30 minutes to completely dissolve it, and place it in a 1°C environment to obtain a 1,3,5-tris(4-aminophenyl)benzene solution for standby use. Prepare a 5w / v% sodium nitrite aqueous solution, wherein the ratio of the amount of sodium nitrite to the amount of 1,3,5-tris(4-aminophenyl)benzene is 7:1. Add the prepared sodium nitrite aqueous solution dropwise to the above-mentioned 1,3,5-tris(4-aminophenyl)benzene solution, maintain the temperature of the 1,3,5-tris(4-aminophenyl)benzene solution at 3°C, and stir for 30 minutes to obtain a diazonium salt solution. A 5 w / v% calcium hydroxide solution was added to the diazonium salt solution. The pH of the diazonium salt solution was adjusted to 6. Dodecylamine was then added at a mass ratio of 0.3:1 between dodecylamine and 1,3,5-tris(4-aminophenyl)benzene. The mixture was stirred thoroughly and set aside. A 4 mol / L pyrogallol / ethyl acetate solution was prepared. The pyrogallol / ethyl acetate solution was added dropwise to the surfactant-containing diazonium salt solution. The mixture was stirred vigorously for 196 hours at 3000 rpm while maintaining the temperature at 3°C. This yielded crude nanosheets with a high specific surface area. The crude nanosheets were separated from the mixed solution by filtration and washed with tetrachloromethane. Finally, the washed nanosheets were dried to yield high-specific surface area nanosheets.

[0069] The resulting high-surface-area nanosheets were dispersed in N,N-dimethylacetamide via ultrasonic treatment. The mass ratio of the high-surface-area nanosheets to the N,N-dimethylacetamide was 5 wt%, and the ultrasonic treatment lasted for 480 minutes, yielding a N,N-dimethylacetamide dispersion of the high-surface-area nanosheets. A 10 wt% polybenzimidazole solution was prepared. The resulting N,N-dimethylacetamide dispersion of the high-surface-area nanosheets was mixed with the polybenzimidazole solution and stirred until the mass ratio of the polybenzimidazole solution was 4.8%, with a nanosheet-to-polymer ratio of 0.2:1. This solution was then used to form a 45-micron-thick blended all-vanadium redox flow battery separator using a tape casting machine.

[0070] The prepared ultrathin nanosheets were tested and their BET specific surface area was 852.3 m 2 g -1 , the pore size is mainly distributed at 0.9 nm, and the thickness of the nanosheet is 3.7 nm.

[0071] Testing the VO2 of blended all-vanadium redox flow battery membrane 2+ The vanadium ion permeability coefficient is 5.61×10 -7 cm 2 min-1 .

[0072] The blended all-vanadium redox flow battery membrane was tested in an all-vanadium redox flow battery at a working current density of 80 mA cm -2 Under constant current charge and discharge conditions, the test results show a coulombic efficiency of 96% and an energy efficiency of 80.6%.

[0073] Figure 4 This is the X-ray diffraction spectrum of the high specific surface area nanosheet of Example 3 of the present invention, which shows that the nanosheet has partial crystallinity, that is, its internal structure is regularly arranged, and thus has a better pore structure.

[0074] Comparative Example 1

[0075] The polybenzimidazole was directly cast into a film, and its thickness was measured to be 60 μm.

[0076] Testing the VO of polybenzimidazole membrane 2+ The vanadium ion permeability coefficient is 8.89×10 -7 cm 2 min -1 .

[0077] Polybenzimidazole was tested in all-vanadium redox flow battery at a working current density of 80 mA cm -2 Under constant current charge and discharge conditions, the test results show a coulombic efficiency of 97.3% and an energy efficiency of 70.2%.

[0078] Comparative Example 2

[0079] The Nafion115 membrane produced by DuPont was used to test the all-vanadium flow battery, and its VO 2+ The vanadium ion permeability coefficient is 15.69×10 -7 cm 2 min -1 , at a working current density of 80 mA cm -2 Under constant current charge and discharge conditions, the test results show a coulombic efficiency of 93.3% and an energy efficiency of 64.1%.

[0080] In summary, the performance of the blended all-vanadium redox flow battery membrane doped with nanosheets is improved. The specific performance improvement is shown in Table 1. Specifically, the blended all-vanadium redox flow battery membrane doped with nanosheets has a high vanadium resistance capacity, and VO 2+ The vanadium ion permeability coefficient is significantly improved without affecting its proton transport capacity.

[0081] Table 1 Vanadium resistance of different diaphragms and performance of all-vanadium redox flow batteries

[0082]

[0083] Obviously, the above embodiments are merely examples for clarity of explanation and are not intended to limit the implementation methods. Those skilled in the art will readily appreciate that other variations or modifications based on the above descriptions are possible. It is not necessary and impossible to enumerate all implementation methods here. Obvious variations or modifications arising therefrom remain within the scope of protection of the present invention.

Claims

1. A method for preparing a nanosheet, characterized in that: The structural formula is shown in Formula 1: The method for preparing a nanosheet comprises: Step (1): adding 1,3,5-tris(4-aminophenyl)benzene monomer to water, adding inorganic acid thereto, mechanically stirring to completely dissolve it, and placing it in an environment of 0 to 10° C. to obtain 1,3,5-tris(4-aminophenyl)benzene solution A; Step (2): adding the prepared sodium nitrite aqueous solution dropwise to the 1,3,5-tris(4-aminophenyl)benzene solution A described in step (1), maintaining the temperature of the 1,3,5-tris(4-aminophenyl)benzene solution A at 0 to 10° C., stirring for 10 to 30 minutes, and obtaining a diazonium salt solution B; Step (3): adding an inorganic base solution to the diazonium salt solution B in step (2), adjusting the pH of the diazonium salt solution B to 1 to 14, then adding a surfactant, and stirring to obtain a diazonium salt solution C; Step (4): preparing a pyrogallol organic solution to obtain an organic solution D; Step (5): adding the organic solution D in step (4) dropwise to the diazonium salt solution C in step (3), stirring vigorously for 0.05 to 240 hours, at a stirring speed of 100 to 8000 rpm, and maintaining the mixed solution at 0 to 10° C., and performing post-treatment to obtain nanosheets, and utilizing the auxiliary effect of a surfactant to make the water-oil two-phase monomers participating in the diazo coupling reaction at the microphase interface uniformly distributed at the interface.

2. The method for preparing a nanosheet according to claim 1, characterized in that: In the step (1), the mass percentage concentration of 1,3,5-tri(4-aminophenyl)benzene monomer is 0.01 to 50 wt%, and the volume fraction of the inorganic acid is 0.01 to 20 v / v%.

3. The method for preparing a nanosheet according to claim 1, characterized in that: The inorganic acid in step (1) is concentrated hydrochloric acid, concentrated sulfuric acid, concentrated nitric acid, or tetrafluoroboric acid.

4. The method for preparing a nanosheet according to claim 1, characterized in that: In the step (2), the ratio of the amount of sodium nitrite to the amount of 1,3,5-tri(4-aminophenyl)benzene is (3-10):

1.

5. The method for preparing a nanosheet according to claim 1, characterized in that: In the step (3), the inorganic alkaline solution is lithium hydroxide, sodium hydroxide, potassium hydroxide, cesium hydroxide, barium hydroxide, calcium hydroxide, ammonium hydroxide, sodium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate or cesium carbonate.

6. The method for preparing a nanosheet according to claim 1, characterized in that: In the step (3), the surfactant is sodium oleate, stearylamine, sodium laurate, coconut amine, sodium stearate, AES, sodium dodecyl sulfate, dodecylamine, sodium dodecylbenzene sulfonate, dodecyltrimethylammonium chloride or dodecyltrimethylammonium bromide.

7. The method for preparing a nanosheet according to claim 1, characterized in that: In the step (3), the mass ratio of the surfactant to the 1,3,5-tris(4-aminophenyl)benzene monomer is (0.001-1):

1.

8. The method for preparing a nanosheet according to claim 1, characterized in that: In the step (4), the concentration of the pyrogallol organic solution is 0.001 to 5 mol / L.

9. Use of the nanosheets obtained by the preparation method of claim 1 in a blended all-vanadium liquid flow battery membrane.

Citation Information

Patent Citations

  • A COF / PBI membrane for vanadium redox flow batteries and its preparation method

    CN110429293B

  • Sandwich structured composite proton exchange membrane, and preparation method and use thereof

    CN105047844A

  • Polymer microsphere / amino containing sulfonated poly(aryl ether ketone sulfone) proton exchange membrane material for fuel cells, and preparation method and application thereof

    CN106751839A